2020
DOI: 10.1590/0100-3984.2020.0051
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound: an additional tool in COVID-19

Abstract: Lung ultrasound is a well-defined diagnostic modality in the point of care emergency medicine concept. In the context of the coronavirus disease 2019 (COVID-19) pandemic, the lung ultrasound assumed an essential role in this disease, with a valid correlation of the imaging results with computed tomography. Recognize how the diagnostic possibilities of ultrasound in the approach of COVID-19 and its differential diagnoses are fundamental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
0
20
0
10
Order By: Relevance
“…In addition, they have a longer acoustic wavelength and provide better penetration and visualization of deeper structures. This type of transducer is, therefore, best suited for evaluating consolidations and pleural effusions [ 27 , 130 ]. On the other hand, high-frequency transducers have a high resolution compared to low-frequency transducers and are more suitable for evaluating the pleural region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they have a longer acoustic wavelength and provide better penetration and visualization of deeper structures. This type of transducer is, therefore, best suited for evaluating consolidations and pleural effusions [ 27 , 130 ]. On the other hand, high-frequency transducers have a high resolution compared to low-frequency transducers and are more suitable for evaluating the pleural region.…”
Section: Methodsmentioning
confidence: 99%
“…Lung ultrasound (LUS) has good sensitivity in detecting lung pathology (bacterial or viral) [ 25 , 26 ]. Regarding COVID-19, studies report a high correlation between the clinical findings of the LUS and the chest CT examination [ 27 , 28 , 29 , 30 , 31 , 32 ]. In this sense, some studies suggest the use of ultrasound as an alternative to auscultation and auxiliary XR and CT exams [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some protocols evaluate 14 areas (two anterior, two lateral and three posterior areas in each hemithorax) and constitute a scoring system based on findings. 48 It was reported that scoring systems based on B-line were correlated with oxygen parameters, and thus, LUS can be used for COVID-19 pneumonia severity estimation. 49 To determine disease severity, a scoring system to avoid subjectivity and the operator-dependence of the exam was suggested by Soldati et al According to this system, normal LUS pattern characterized by regular pleural line and A-lines is score 0 vertical artifacts are described.…”
Section: Of Lus In Covid-19 Pneumoniamentioning
confidence: 99%
“…In the previous issue of the Radiologia Brasileira, the text “Pulmonary ultrasound: an additional tool in COVID-19” ( 15 ) was published as a special article on the use of chest ultrasound in COVID-19, presenting the technique, normal findings, disinfection, main findings, and limitations as a screening method. Chest ultrasound is an additional tool in emergency care.…”
mentioning
confidence: 99%
“…The use of imaging methods to diagnose and control treatment in COVID-19 illustrates the central role of imagology in medicine. The special article by Oliveira et al ( 15 ) improves the knowledge of the several ultrasound uses in the fight against COVID-19 .This method, as a medical act, should be thought of as a foundation by the general radiologist.…”
mentioning
confidence: 99%